Homeschooling services for mildly mentally retarded children at the Aulia Rahmah Hasanah Orphanage Foundation, Balikpapan - Mochamad Sulaiman; Fandi Afrizal; Firatih Tandiboro; Nugroho Ari Sadewo; Saqila Aulia; Tasya Dwiyanti; Prambudiana Prambudiana; Yongi Stiyo Pangestu; Adji Muhammad Taqwa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
This article is based on the Program Abdi Mengajar (PAM) which seeks to find solutions to the problems faced by the Aulia Rahma Hasanah orphanage foundation which is located in the Kelurahan Karang Joang, Balikpapan Utara. The main problem faced by partners is the lack of funds and human resources to provide proper education to foster children, especially in formal education services. There is exists learning barriers that affect mentally disturbed children or commonly called intellectual disabilities. therefore in this community service activity, the concept of homeschooling services is designed to be able to provide knowledge, especially in the social field. The purpose of this community service activity is specifically help to improve the communication and socialization skills of mentally retarded children and provide supplementary informal educational services. From the activities that have been carried out, there have been positive developments related to attitudes and mental knowledge by foster children, although not significant enough. Continuous and intensive activities are still needed so that they can provide better benefits for the mental development and knowledge of mentally retarded children until they are completely healed.